1986
DOI: 10.1159/000199373
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Enzyme Transfer in Sodium Taurocholate-Induced Acute Hemorrhagic Pancreatitis

Abstract: The pathways of enzyme transfer from the pancreas into the systemic circulation were analyzed in sodium taurocholate-induced acute hemorrhagic pancreatitis in the rat by estimating lipase concentrations in blood, lymph and ascites. During the first few hours of pancreatitis high enzyme levels were observed in thoracic duct lymph. However, cannulation of the thoracic duct did not prevent a significant increase in the lipase concentration in peripheral blood. The portal vein lipase concentration was found to exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Since then, many evidences have been accumulated that confirm how lymphatics represent a pathway for enzymes overflowed in the interstitial tissue in experimental pancreatitis. Godart (1965) showed that tracers can be found in the lymph vessels only 15 min after their injection in the duct system, and the levels of pancreatic enzymes in the lymph of the thoracic duct increase dramatically within the first few hours from the induction of the pancreatitis (Sim et al, 1966; Lange et al, 1986). In such conditions the lymphatic system seems to be able to drain, together with the enzymes, also fragments of cells and erythrocytes (Bockman et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, many evidences have been accumulated that confirm how lymphatics represent a pathway for enzymes overflowed in the interstitial tissue in experimental pancreatitis. Godart (1965) showed that tracers can be found in the lymph vessels only 15 min after their injection in the duct system, and the levels of pancreatic enzymes in the lymph of the thoracic duct increase dramatically within the first few hours from the induction of the pancreatitis (Sim et al, 1966; Lange et al, 1986). In such conditions the lymphatic system seems to be able to drain, together with the enzymes, also fragments of cells and erythrocytes (Bockman et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…The periacinar space is identified as an important watershed: it communicates with basal intercellular clefts, terminal ramifications of the pancreatic duct system, pancreatic venules, interstitium and – once pancreatitis begins – the centroacinar space [76]. Collectively, these and other studies show that the diagnostic rise in the concentration of pancreatic enzymes in peripheral blood results initially from products that enter the portal vein, but that the lymphatic system which drains the interstitium and peripancreatic fluid is a major contributor thereafter, as also is the transperitoneal route [71, 77, 78, 79, 80]. …”
Section: Back To the Futurementioning
confidence: 99%
“…From the 1960s, the clinical importance of ascitic fluid in acute pancreatitis was noted [1][2][3][4], and Pickford et al [5] initially reported a relationship between abdominal paracentesis and peritoneal lavage at the time of diagnosis and the prognosis of human acute pancreatitis. Other than diagnostic values, many investigators followed Ranson's report [6] showing the therapeutic efficacy of peritoneal lavage.…”
Section: Introductionmentioning
confidence: 99%